Eksplorasi Etnomatematika pada Kerajinan Cowek di Pasuruan - Muthmainnah; Susanti, Elly; Marhayati, Marhayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to explore the ethnomathematical concepts embedded in the traditional cowek handicraft produced in Randusari Village, Gadingrejo District, Pasuruan Regency, Indonesia. The research employed a qualitative approach using observation, interviews, documentation, and literature review as data collection techniques. The research participants consisted of local cowek artisans who possessed extensive experience in the traditional production process. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings revealed that the cowek-making process incorporates various mathematical concepts, including direct proportion in determining the composition of raw materials, measurement in production activities, arithmetic sequences in the variation of cowek sizes, the concept of circles in the basic geometric form of the cowek, and the concept of solids of revolution whose volume can be modeled using integral calculus. These findings indicate that cowek handicrafts have significant potential as a culturally responsive mathematics learning resource that can enhance students’ contextual understanding of mathematical concepts while preserving local cultural heritage. Keywords: Ethnomathematics; Cowek Handicraft; Local Culture